2020
DOI: 10.3389/fmars.2020.570361
|View full text |Cite
|
Sign up to set email alerts
|

The Small Giant Clam, Tridacna maxima Exhibits Minimal Population Genetic Structure in the Red Sea and Genetic Differentiation From the Gulf of Aden

Abstract: The Red Sea serves as a natural laboratory to investigate mechanisms of genetic differentiation and population dynamics of reef organisms due to its high species endemism. Giant clams, important yet understudied coral reef engineering species, are ideal candidates for such study in this region. This paper presents the first population genetics study of giant clams covering the entire East coast of the Red Sea. Our study aimed to investigate the population structure of the small giant clam, Tridacna maxima, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 82 publications
(107 reference statements)
2
11
2
Order By: Relevance
“…Occasional confusion of T. maxima and T. squamosa have been also previously suspected for the Red Sea (Pappas et al, 2017). However, as the same observers as in the present study, reached a very high and genetically confirmed accuracy in previous species-targeted sampling (Lim et al, 2020), and since the presented ratio of 89% T. maxima and 11% T. squamosa clams corresponds to past reports on species allocation in the region (Jantzen et al, 2008;Pappas et al, 2017), we are confident that presented numbers actually reflect what can be found in Red Sea coral reefs.…”
Section: Overall Abundance Of Tridacna Sppsupporting
confidence: 83%
See 1 more Smart Citation
“…Occasional confusion of T. maxima and T. squamosa have been also previously suspected for the Red Sea (Pappas et al, 2017). However, as the same observers as in the present study, reached a very high and genetically confirmed accuracy in previous species-targeted sampling (Lim et al, 2020), and since the presented ratio of 89% T. maxima and 11% T. squamosa clams corresponds to past reports on species allocation in the region (Jantzen et al, 2008;Pappas et al, 2017), we are confident that presented numbers actually reflect what can be found in Red Sea coral reefs.…”
Section: Overall Abundance Of Tridacna Sppsupporting
confidence: 83%
“…For the Red Sea, three species of giant clams have been previously reported (e.g., by Roa-Quiaoit, 2005;Richter et al, 2008;Huber and Eschner, 2010;Ullmann, 2013), namely Tridacna squamosa Lamarck, 1819, Tridacna squamosina Sturany, 1899 (previously described as T. costata by Richter et al, 2008) and Tridacna maxima Röding, 1789. The latter, also called the "small giant clam, " is assumed to be the most abundant giant clam species in the Red Sea (Jantzen et al, 2008;Pappas et al, 2017;Lim et al, 2020). Previously reported densities of T. maxima vary substantially, with typical averages ranging between 10 −4 and 10 −5 individuals per meter square (m 2 ), in different regions of the Indo-Pacific .…”
Section: Introductionmentioning
confidence: 99%
“…The observed site‐specific structure of the Red Sea giant clam‐Symbiodiniaceae associations contrasts with the recently reported population structure of the T. maxima host. Current evidence points toward a genetic disparity between the Red Sea T. maxima clams and other populations from the West Indian Ocean (Fauvelot et al., 2020), but that the population inside the Red Sea is characterized by high gene flow among regions and panmixia (Lim et al., 2020). Yet, Lim et al, also observed a high level of host haplotypic diversity within the Red Sea population of T. maxima (i.e., a number of haplotypes at each site), which contrasts with the observed homogeneity of the associated Symbiodiniaceae assemblages that we identified here, especially in the more southern sites.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to corals, where more fine‐scale resolutions increasingly reveal a relatively specific host genotype‐determined algal assemblage, such flexibility in clams represents, if confirmed, a mechanism conferring giant clams an additional resilience to warming. Indeed, although coral reefs in the Red Sea, particularly those in the southern Red Sea, have experienced intense warming‐induced bleaching in the past, such mass bleaching events have not been reported for Red Sea T. maxima populations (Lim et al., 2020). Testing this hypothesis would require experimental assessment of thermal performance of T. maxima under concurrent manipulation of their symbionts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation